Evaluating trade-offs between agricultural productivity and long-term ecosystem services provision among maize farmers practising conventional and conservation agriculture in Kafue Zambia - Mungatana, Eric D. (University of Pretoria, 2017)
Dissertation (MSc (Agric))--University of Pretoria, 2016.